2021
DOI: 10.1002/brb3.2226
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan in the diet ameliorates motor deficits in a rotenone‐induced rat Parkinson's disease model via activating the aromatic hydrocarbon receptor pathway

Abstract: Background and purpose: Parkinson's disease (PD), a common neurodegenerative disorder with motor and nonmotor symptoms, does not have effective treatments.Dietary tryptophan (Trp) supplementation has potential benefits for the treatment of multiple disorders. However, whether additional Trp in the diet could be beneficial for PD remains to beinvestigated. In the present study, the neuroprotective role of dietary Trp on a rotenone-induced rat model of PD was determined. Methods:The rotenone was injected to buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Locomotor dysfunction serves as a wide-acknowledged clinical symptom of PD [23]. In our previous study, we observed that dietary tryptophan can ameliorate the impaired motor function in PD [47], in the current study, we revealed that MA-5 can promote the recovery of the motor function in mice induced by MPTP via activating the AMPK-mediated autophagy.…”
supporting
confidence: 60%
“…Locomotor dysfunction serves as a wide-acknowledged clinical symptom of PD [23]. In our previous study, we observed that dietary tryptophan can ameliorate the impaired motor function in PD [47], in the current study, we revealed that MA-5 can promote the recovery of the motor function in mice induced by MPTP via activating the AMPK-mediated autophagy.…”
supporting
confidence: 60%
“…Chronic exposure to both chemicals has been linked to the development of Parkinson’s disease (PD) in mice, rats and humans ( 14 ). In a manner similar to haloperidol, dietary tryptophan improves the impaired motor functions in rotenone-induced rat models of PD ( 15 ). The benefits of tryptophan in animals exposed to haloperidol, rotenone and paraquat, along with the sensitivity of yeast trp Δ/ aro Δ mutants to all 3 compounds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR), often referred to as the dioxin receptor, is a ligand-activated transcription factor that is widely expressed centrally and systemically. AHR signaling is thought to be an important component of the barrier site immune response and can regulate a variety of cellular processes, including immune regulation, cell development, differentiation, proliferation, survival, and apoptosis ( 110 , 111 ). AhR forms a protein complex with dimer of the 90 kDa heat shock protein (HSP90), AhR-interacting protein (AIP), the co-chaperone p23, and the protein kinase SRC, which is expressed in the cytoplasm ( 112 ).…”
Section: Regulation Of Trp Metabolism On Downstream Targetsmentioning
confidence: 99%
“…The collection of urine samples is also simpler than that of blood or cerebrospinal fluid, making urine detection a non-invasive and accessible method. Yilin Wang ( 111 ) found that TRP supplementation inhibited nuclear translocation of NF-κB in a PD model. However, With the use of AhR pathway inhibitors, TRP’s neuroprotective effects and its suppression of NF-κB were reversed.…”
Section: Trp Metabolism In Neurological and Psychiatric Disordersmentioning
confidence: 99%